Regulating the SADC Regional Railway Corridors for Investments - Lubinda M. Sakanga; Erastus M. Mwanaumo; Wellington D. Thwala (Journal of Transport and Supply Chain Management, 2024)
Background: According to the Southern African Development Community (SADC) the Southern African railway network extends homogenously through 1067mm cape gauge across 12 of the 15 SADC nations. Nonetheless, the network is constrained from efficient and effective operation due to insufficient investment in maintaining and upgrading affected tracks and equipment apart from inadequate human capital. This article presents the case of regulation as a plausible solution.